Business feasibility assessment of a samarinda car rental business: financial and marketing perspectives - Surahman Surahman; Nasywa Nur Fatiya; Imelda Irawan; Putri Widya Hastuti; Prapdop Prapdopo (Institute of Computer Science (IOCS), 2025)
This study analyzes the business feasibility of a car rental company in Samarinda from financial and marketing perspectives. The increasing mobility needs of the people in Samarinda have driven the growth of the transportation service industry, including car rentals, making this analysis timely and relevant. A mixed methods approach was applied, combining qualitative interviews and quantitative financial data. Financial feasibility was evaluated using Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Net Benefit-Cost Ratio (Net B/C) indicators, supported by a sensitivity analysis to assess the business’s resilience to changes in the discount rate. The results indicate that PT Mitra Trans Bersaudara is financially feasible, with a positive NPV of IDR 142,498,446, an IRR of 13.87% exceeding the 10–12% discount rate, a Net B/C ratio of 1.069, and a Payback Period of 2.33 years. Marketing analysis through STP (Segmentation, Targeting, and Positioning) and the 7Ps Marketing Mix revealed key segments, including companies, government institutions, and upper-middle-class families, with a strong positioning as a trusted and professional service provider. This research contributes as a reference for future studies, a benchmark for car rental businesses, and a consideration for government policies in supporting the local transportation sector.